2022
DOI: 10.3897/pharmacia.69.e89400
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking investigation of anti-inflammatory herbal compounds as potential LOX-5 and COX-2 inhibitors

Abstract: According to the World Journal of Gastroenterology, more than 5 million people worldwide suffer from inflammatory bowel disease. The use of phytotherapeutic remedies in treatment of chronic inflammatory processes can be an effective alternative in patient’s therapy. The advantage of herbal medicines is the ability to influence various links of pathogenesis, lack of addiction, and the absence of withdrawal syndrome with long-term use in chronic pathology. In order to develop a new combined remedy with anti-infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…AKBA showed a binding energy of -9. We have reproduced the docking studies performed by Vyshnevska [66] and found the interactions with the same amino acids with a Glide score of -5,94 Kcal/mol and dGbind of -37,42 Kcal/mol (Figure 6 and Table 3). Que displays a better docking score and MMGBSA dG Bind in comparison with those of AKBA, -3,37 kcal/mol and -28,21 kcal/mol, respectively.…”
Section: Lipoxygenasesupporting
confidence: 61%
See 1 more Smart Citation
“…AKBA showed a binding energy of -9. We have reproduced the docking studies performed by Vyshnevska [66] and found the interactions with the same amino acids with a Glide score of -5,94 Kcal/mol and dGbind of -37,42 Kcal/mol (Figure 6 and Table 3). Que displays a better docking score and MMGBSA dG Bind in comparison with those of AKBA, -3,37 kcal/mol and -28,21 kcal/mol, respectively.…”
Section: Lipoxygenasesupporting
confidence: 61%
“…Vyshnevska et al [66] have performed molecular docking investigations on herbal compounds, including Que, as potential 5-LOX and COX-2 inhibitors. Concerning 5-LOX, (PDB code 6NCF) [67] was chosen, and the simulations were carried out with AutoDock Vina.…”
Section: Lipoxygenasementioning
confidence: 99%
“…In their study they included the bioactive molecules from U. dioica and other plants known to posses anti-inflammatory activity, such as Foeniculum vulgare , Acorus calamus , Potentilla palustris , Petroselinum crispum , Inula helenium , Bergenia crassifolia , Veronica officinalis , Carum carvi , Levisticum officinale , Cichorium intybus , Capsella bursa-pastoris , and Equisetum arvense . Among the studied compounds and following the docking carried out using AutoDock Vina, the authors identified some polyphenols as promising binders [ 45 ]. This aspect was also described by Idris et al in their contribution in which they investigated polyphenols as ligands for 5-LOX and COX-2 [ 46 ].…”
Section: The Neuroprotective Potential Of U Dioicamentioning
confidence: 99%
“…Ellagic acid represent another example of polyphenolic compound contained in U. dioica [ 14 ]. The molecule was highlighted as a potential hit by this screening [ 45 ]. Similarly, a compound named urticin A, a secolignal isolated from Urtica rhizomes [ 48 ], was described among the best potential binders for both 5-LOX and COX-2, according to computational studies [ 45 ].…”
Section: The Neuroprotective Potential Of U Dioicamentioning
confidence: 99%
See 1 more Smart Citation